Switching From Reference Adalimumab to SB5 (Adalimumab Biosimilar) in Patients With Rheumatoid Arthritis: Fifty-Two-Week Phase III Randomized Study Results - Weinblatt, Michael E; Baranauskaite, Asta; Dokoupilova, Eva; Zielinska, Agnieszka; Jaworski, Janusz; Racewicz, Artur; Pileckyte, Margarita; Jedrychowicz-Rosiak, Krystyna; Baek, Inyoung; Ghil, Jeehoon (Arthritis & rheumatology (Hoboken, N.J.), 2018)
OBJECTIVE: The 24-week equivalent efficacy and comparable safety results of the biosimilar SB5 and reference adalimumab (ADA) from the phase III randomized study in patients with moderate-to-severe rheumatoid arthritis (RA) have been reported previously. We undertook this transition study to evaluate patients who switched from ADA to SB5 or who continued to receive SB5 or ADA up to 52 weeks. METHODS: In this phase III study, patients were initially randomized 1:1 to receive SB5 or ADA (40 mg subcutaneously every other week). At 24 weeks, patients receiving ADA were rerandomized 1:1 to continue with ADA (ADA/ADA group) or to switch to SB5 (ADA/SB5 group) up to week 52; patients receiving SB5 continued with SB5 for 52 weeks (SB5 group). Efficacy, safety, and immunogenicity were evaluated up to 52 weeks. RESULTS: The full analysis set population consisted of 542 patients (269 in the SB5 group, 273 in the ADA overall group [patients who were randomized to receive ADA at week 0], 125 in the ADA/SB5 group, and 129 in the ADA/ADA group). The percentages of patients meeting the American College of Rheumatology 20%, 50%, or 70% improvement criteria (achieving an ACR20, ACR50, or ACR70 response) at week 24 were maintained after the transition from ADA to SB5, and these response rates were comparable across treatment groups throughout the study. ACR20 response rates ranged from 73.4% to 78.8% at week 52. Radiographic progression was minimal and comparable across treatment groups. The safety profile and the incidence of antidrug antibodies were comparable across treatment groups after transition. CONCLUSION: SB5 was well tolerated over 1 year in patients with RA, with efficacy, safety, and immunogenicity comparable to those of ADA. Switching from ADA to SB5 had no treatment-emergent issues such as increased adverse events, increased immunogenicity, or loss of efficacy.
Keywords: Humans; lidé středního věku; Arthritis, Rheumatoid; Double-Blind Method; biosimilární léčivé přípravky; antirevmatika; Female; dospělí; náhrada léků; výsledek terapie; dvojitá slepá metoda; lidé; časové faktory; Adalimumab; Drug Substitution; revmatoidní artritida; Adult; ženské pohlaví; stupeň závažnosti nemoci; Male; Middle Aged; Treatment Outcome; Severity of Illness Index; mužské pohlaví; Time Factors; Biosimilar Pharmaceuticals; Antirheumatic Agents; adalimumab